METAL COMPLEX-BASED CHEMOSENSORS FOR SELECTIVE SENSING OF BIOLOGICALLY AND ENVIRONMENTALLY SIGNIFICANT IONS - Ghosh, Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Chemosensors based on metal complexes are advanced analytical tools designed to detect and quantify specific ions or molecules in various environments. Among the various types, metal complex-based chemosensors have garnered considerable attention due to their high sensitivity, selectivity, and versatility. These chemosensors employ metal complexes as the core sensing units, taking advantage of their unique coordination chemistry and photophysical properties to achieve selective sensing of biologically and environmentally significant ions. The metal center typically interacts with the analyte, causing a measurable change in the sensor's physical or chemical properties, such as fluorescence, color, or electrical conductivity. This interaction results in high selectivity and sensitivity, making metal complex-based chemosensors ideal for applications in environmental monitoring, biomedical diagnostics, and industrial process control. Their versatility, coupled with the ability to tailor the metal-ligand coordination chemistry, enables precise detection of biologically and environmentally significant ions, contributing to advancements in both scientific research and practical applications.